Categorization of Self-regulated Learning in Pancasila Education Learning at Elementary School - Erma Fitri Astuti; Rahayu Condro Murti (Universitas Pendidikan Ganesha, 2024)
Self-regulated learning is a form of character. The character of self-regulated learning of elementary school students can be formed through Pancasila Education. This study aims to describe self-regulated learning in Pancasila Education learning of fifth grade elementary school students. This research is descriptive type with quantitative approach. The research method used in this study is the survey method. Data collection was done with a self-regulated learning questionnaire instrument. The self-regulated learning instrument in this study has 20 questions with 6 indicators, independence from others, have self-confidence, discipline behavior, has a sense of responsibility, behave on their own initiative, do a self-control. The instrument used has been tested for validity and reliability. The reliability test with Cronbach's alpha obtained a score of 0.873. Data was collected using a 1-5 Likert scale questionnaire. Data were analyzed descriptively which included 6 indicators with categories of very good, good, enough, less, and very less. The results showed that the overall average of students' self-regulated learning in Pancasila Education was 67% which was obtained from 29 students who filled out the self-regulated learning questionnaire. It is concluded that the self-regulated learning of fifth grade students of the elementary school is in the good category. However, there are differences in independence in each indicator. This means that students' learning independence in Pancasila Education needs to be improved again, so that each indicator in self-regulated learning can be achieved well.